2022
DOI: 10.3233/jad-210480
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in T-Cell Transcription Factors and Cytokine Gene Expression in Late-Onset Alzheimer’s Disease

Abstract: Background: Late-onset Alzheimer’s disease (LOAD) is associated with many environmental and genetic factors. The effect of systemic inflammation on the pathogenesis of neurodegenerative diseases such as AD has been strongly suggested. T helper cells (Th) are one of the important components of the immune system and can easily infiltrate the brain in pathological conditions. The development of each Th-subset depends on the production of unique cytokines and their main regulator. Objective: This study aimed to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…However, yet another review on peripheral IL-1β, IL-6, TNF-α, and CRP found no statistically significant difference between AD patients and controls in any of these markers [ 116 ]. A possible explanation for this discrepancy is that the meta-analysis by Ng et al included far fewer studies than that by Lai et al Still, Nesham et al reported the opposite trend in a study of 60 subjects, in which mRNA levels of IFN-γ and TNF-α in PBMCs of AD subjects were, instead, decreased compared with non-demented controls [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, yet another review on peripheral IL-1β, IL-6, TNF-α, and CRP found no statistically significant difference between AD patients and controls in any of these markers [ 116 ]. A possible explanation for this discrepancy is that the meta-analysis by Ng et al included far fewer studies than that by Lai et al Still, Nesham et al reported the opposite trend in a study of 60 subjects, in which mRNA levels of IFN-γ and TNF-α in PBMCs of AD subjects were, instead, decreased compared with non-demented controls [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 40% of Fahr's disease patients initially present with neuropsychiatric features ranging from mild di culties in concentration and memory to changes in personality, behaviors, psychosis, or dementia (10,11). The speci c manifestation depends on the age of disease onset, with schizophreniform psychosis without neurological features being more prevalent in younger individuals (20-40 years) and dementia and movement disorders being common in later-onset cases (mean age of onset at 49 years) (12).…”
Section: Discussionmentioning
confidence: 99%
“… 61 Moreover, they can play a key role in the activation or inhibition of AD-related signaling pathways. 62 - 64 The KEGG results showed that the pathways of LDP in the treatment of AD were mainly enriched in the B cell receptor-signaling pathway and in HIV-1 and HCMV infections. Studies have shown that activated B cells can not only induce the differentiation of effector T cells and lead to neuroinflammation 65 - 67 but also participate in the pathological process of AD by secreting cytokines and acting on other immune cells (such as macrophages).…”
Section: Discussionmentioning
confidence: 99%